Spermidine as a promising anticancer agent: Recent advances and newer insights on its molecular mechanisms - Prasher, Parteek; Sharma, Mousmee; Singh, Sachin Kumar; Gulati, Monica; Chellappan, Dinesh Kumar; Rajput, Rashi; Gupta, Gaurav; Ydyrys, Alibek; Kulbayeva, Marzhan; Abdull Razis, Ahmad Faizal; Modu, Babagana; Sharifi-Rad, Javad; et al. (Frontiers in Chemistry, 2023)
Spermidine, a naturally occurring polyamine compound found in semen and several plant sources, has a remarkable biological profile, particularly its anticancer properties. Spermidine helps to control the cancer pathogenesis by halting the cell cycle, inhibiting tumour cell proliferation, and suppressing tumor growth. It also triggers autophagy by regulating key oncologic pathways. The increased intake of polyamines, such as spermidine, can suppress oncogenesis and slow the growth of existing tumors due to its role in anticancer immunosurveillance and regulation of polyamine metabolism. The spermidine/spermine N-1-acetyltransferase (SSAT) enzyme, which plays a critical role in polyamine homeostasis, can serve as a diagnostic marker in human cancers. Additionally, chemically modified derivatives of spermidine hold great potential for prognostic, diagnostic, and therapeutic applications against various malignancies. In this review, we will explore the anticancer properties of spermidine in detail.